Separation of ash and sulfur dioxide during the 2011 Grímsvötn eruption - Moxnes, E.D. E.D.; Kristiansen, Nina N.I.; Stohl, Andreas; Durant, Adam; Clarisse, Lieven; Weber, Konradin; Vogel, Andreas (2014)
Modeling the transport of volcanic ash and gases released during volcanic eruptions is crucially dependent on knowledge of the source term of the eruption, that is, the source strength as a function of altitude and time. For the first time, an inversion method is used to estimate the source terms of both volcanic sulfur dioxide (SO2) and ash. It was applied to the explosive volcanic eruption of Grímsvötn, Iceland, in May 2011. The method uses input from the particle dispersion model, FLEXPART (flexible particle dispersion model), a priori source estimates, and satellite observations of SO2 or ash total columns from Infrared Atmospheric Sounding Interferometer to separately obtain the source terms for volcanic SO2 and fine ash. The estimated source terms show that SO2 was emitted mostly to high altitudes (5 to 13 km) during about 18 h (22 May, 00-18 UTC) while fine ash was emitted mostly to low altitudes (below 4 km) during roughly 24 h (22 May 06 UTC to 23 May 06 UTC). FLEXPART simulations using the estimated source terms show a clear separation of SO2 (transported mostly northwestward) and the fine ash (transported mostly southeastward). This corresponds well with independent satellite observations and measured aerosol mass concentrations and lidar measurements at surface stations in Scandinavia. Aircraft measurements above Iceland and Germany confirmed that the ash was located in the lower atmosphere. This demonstrates that the inversion method, in this case, is able to distinguish between emission heights of SO2 and ash and can capture resulting differences in transport patterns. Key Points Ash and SO2 source terms estimated using inverse techniques and satellite data The transport and separation of ash and SO2 are modeled Model simulations correspond well with a range of independent observations ©2014. The Authors. SCOPUS: ar.j SCOPUS: ar.j info:eu-repo/semantics/published